Scholars at War Australasian Social Scientists, 1939-1945 - Gray, Geoffrey; Munro, Doug; Winter, Christine (ANU Press, 2012)
Scholars at War is the first scholarly publication to examine the effect World War II had on the careers of Australasian social scientists. It links a group of scholars through geography, transnational, national and personal scholarly networks, and shared intellectual traditions, explores their use, and contextualizes their experiences and contributions within wider examinations of the role of intellectuals in war. Scholars at War is structured around historical portraits of individual Australasian social scientists. They are not a tight group; rather a cohort of scholars serendipitously involved in and affected by war who share a point of origin. Analyzing practitioners of the social sciences during war brings to the fore specific networks, beliefs and institutions that transcend politically defined spaces. Individual lives help us to make sense of the historical process, helping us illuminate particular events and the larger cultural, social and even political processes of a moment in time. Contributors include Peter Hempenstall, JD Legge, Jock Phillips, John Pomeroy, Cassandra Pybus, David Wetherell, Janet Wilson.